THE MECHANISM OF THE CURRENT INVESTMENT PLANNING IN THE MANAGING OF THE ECONOMIC SECURITY OF AN ENTERPRISE - Sholokhov, Sergey A.; Laptev, Dmitry N. (The journal of contemporary issues in business and government, 2021)
This paper is focused on investment planning in the enterprise economic security management. The actuality of the research is determined by the need for the identification and usage of the adaptation enterprise system in Russia in the current circumstances of the domestic problems and changes in the world economic relations. In work was formed the mechanism of realization the current investing planning (CIP). Besides, authors have highlighted the stages that provide factors of economic security of an enterprise in a short- and medium-term perspective. The research aim is in the development of the mechanism of the practical realization of the current investment planning on the base of its logical structure and the investment program of the business entity. The methodological base of the research was: the dialectical materialistic method, the method of the unity of logical and historical, the methods of the induction and deduction, analytical groups and also such scientific methods as the analysis and synthesis, the logic, the graphic method of the information interpretation.